Can an intervention designed to reduce repetitive negative thinking alter the response to a psychosocial stressor? A randomized controlled study - Funk, Julia; Takano, Keisuke; Babl, Marina; Goldstein, Rebecca; Oberwestersberger, Regina; Kopf-Beck, Johannes; Rohleder, Nicolas; Ehring, Thomas (Behaviour Research and Therapy, 2024)
Prior research suggests that repetitive negative thinking (RNT) negatively impacts mental health by intensifying and prolonging emotional reactivity to stress. This study investigated whether an intervention designed to reduce RNT alters emotional reactivity. Young adults with high trait RNT (N = 79) were randomly allocated to an RNT-focused intervention (smartphone app-based, 10 days) or a waiting list before exposure to a standardized stressor. The pre-registered analysis did not reveal a significant condition * time interaction for negative affect. However, exploratory analyses showed that whilst initial increases in negative affect in response to the stressor did not differ between conditions, participants in the intervention condition reported less negative affect throughout the following recovery phase. Additionally, participants in the intervention condition appraised their ability to cope with the stressor as higher and reported less RNT in the recovery phase. In contrast, the intervention did not affect biological stress responses. The findings indicate that RNT-focused interventions might have positive effects on mental health by breaking the self-reinforcing cycle of RNT, negative affect and maladaptive appraisals in response to stress. However, as findings are partly based on exploratory analyses, further research is needed to confirm whether reduced subjective stress reactivity mediates the effects of RNT-focused interventions on psychopathological symptoms.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Digital interventions; Emotional reactivity; Repetitive negative thinking; Stress response